2019
DOI: 10.1016/j.jbtep.2018.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Does rumination mediate the relationship between attentional control and symptoms of depression?

Abstract: Background and objectives It has been suggested that impaired attentional control (AC) promotes the use of maladaptive emotional regulation strategies, such as rumination, with subsequent increase in risk of depression. Method This study examined this hypothesis in a healthy community sample. Questionnaire measures of depression, anxiety, rumination and self-reported AC (shifting and focusing) were used, as well as an attention performance task (Attention Network Task; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 43 publications
3
36
2
1
Order By: Relevance
“…21,22 COVID-19-related ruminative thoughts may lead people to be immersed in this stressful situation, which further increases psychological symptoms. 15 Several cross-sectional 23,24 and longitudinal studies 18,21 have found that rumination positively predicts anxious and depressive symptoms. Thus, this study proposed that:…”
Section: Rumination As a Potential Mediatormentioning
confidence: 99%
“…21,22 COVID-19-related ruminative thoughts may lead people to be immersed in this stressful situation, which further increases psychological symptoms. 15 Several cross-sectional 23,24 and longitudinal studies 18,21 have found that rumination positively predicts anxious and depressive symptoms. Thus, this study proposed that:…”
Section: Rumination As a Potential Mediatormentioning
confidence: 99%
“…Recent findings suggest that individuals with impaired attentional control engage in maladaptive emotion regulation strategies (i.e., rumination, compulsive thought processes) and are rendered more prone to the risk of depression and anxiety disorders ( DeJong et al, 2019 ). The default mode network (DMN) is a large and distributed network comprised of the posterior cingulate cortex (PCC), medial prefrontal cortex (mPFC), medial and lateral temporal lobes, superior and inferior frontal gyri, and the posterior inferior parietal lobule ( Gusnard et al, 2001 ; Raichle, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding our study, the transient tDCS neural boost within the left dlPFC may only benefit those who do require such a neural boost. Prior research indeed reported that individuals with depression or elevated trait anxiety exhibited impairments in the executive conflict network of attention (e.g., DeJong et al, 2019;Hammar et al, 2019;Wang et al, 2020) as well as reduced activation of the dlPFC when performing tasks involving such a network (e.g., Bishop et al, 2009;De Raedt & Koster, 2010;Hu et al, 2017;Wang et al, 2008). Thus, it is not surprising that we should consider the severity of depressive symptoms and trait anxiety for our effects to appear.…”
Section: Discussionmentioning
confidence: 72%